(untitled) (Global Journal of Human-Social Science, 2020)
This article presents an eidetic investigation that aimed at the production of a narrativizing sense of the coexistence, which is presented as a humanistic contribution to the suturing of the conjunctural emptiness of it. For this, six eidetic dimensions were brought to the front that are part of the shared objective world, and therefore are repetitive structures that make up the underlying continuity of the interruption of coexistence, aspecting the latter. Such dimensions, in the mode of eidetic successiontension between Apollo-Dionysus, rational thought-magic thought, paranoid schizoid position-depressive position, polis-urbs, death-birth and leisure-weariness, are made up of various eidetic conjunctionsdisjunctions developed in the text, and they emerge from the continuity-dispute between images of the technical and psychic-cultural world with its correlative mass society and urban tribal society.